Implementation of Digital Marketing on Saladbar By Hadikitchen Using Social Media and E-Commerce - Golan Hasan; Elviana Elviana (ConCEPt - Conference on Community Engagement Project, 2023)
In daily needs, there are lots of activities that are carried out by everyone, with activities that are increasingly crowded, making many people need additional food intake that is beneficial for the health of the body. The food available on the market today is indeed diverse, but generally it is not typical Indonesian food. People are currently trying to consume healthy food, it must become a habit so that the health of the body is maintained. This is done by choosing natural and fresh foods, without preservatives. One of the healthy foods that are safe to eat is salad. The purpose of implementing and compiling this practical work is to carry out digital marketing and utilize digital tools or media to reach target consumers quickly, precisely and broadly. Apart from that, it can also be more effective and efficient in carrying out promotional strategies through digital marketing for business purposes, increasing brand awareness with the aim of introducing Saladbar By Hadikitchen to the public, so as to produce a strategy in the form of advertising and digital marketing whose results can be used as a benchmark successful or not, the strategy used to increase sales as much as possible. The author collects data by visiting and conducting direct interviews with company owners. The results of implementing digital marketing strategies are very effective in utilizing Instagram social media which can increase followers, sales and build awareness among the people of Batam City.